1001 legal words you need to know - Feinman, Jay M.; Clapp, James E. (James Edward), 1943- (Oxford ; New York : Oxford University Press, 2003)
1001 Legal Words You Need to Know is a comprehensive guide to the language of the American legal system. What is the difference between murder and manslaughter? What's a tort and how do you reform it? Is it slander, or libel (and does it matter if it's even true)? What is due process? And how do you habeas a corpus? 1001 Legal Words You Need to Know explains and illuminates the most difficult and arcane vocabulary any American has to deal with -- that of the law. In this comprehensive guide to the language of the American legal system that doesn't condescend, every term is carefully defined and explained with a sample sentence, and many have supplementary notes. In addition, the book includes ten quick legal problem miniguides, including information on understanding wills, trusts, and inheritance, making a living will, giving someone power of attorney, understanding contracts, what to do if you're sued -- or suing, how to choose a lawyer, exploring law school, and enjoying lawyer shows.
1001 legal words you need to know -- Choosing a lawyer -- How to understand a contract -- The common law and the civil law -- Making a living will -- What is power of attorney? -- Thinking about law school -- What is legal ethics? -- What to do if you're being sued -- Understanding wills, trusts, and intestate succession -- Watching lawyer shows -- Legal aid organizations.
Includes bibliographical references (p. 235-239).
Keywords: Law -- United States -- Dictionaries